A novel shock wave lithotripsy system - Wang, Jen-Chieh (Nanyang Technological University, 2016)
The kidney stone is a worldwide and painful disease. Since the 1980s, shock wave lithotripsy has achieved great success in treating the kidney stone. The main mechanisms of stone comminution are stresses and cavitation induced by the focused shock wave. Although the products of lithotripter have been kept improved in the past three decades, the new ones provide few improvements compared to the first-generation lithotripter. Furthermore, retreatment, remained stone fragments, and renal injury are commonly observed in clinical shock wave lithotripsy. Therefore, innovation of current technique and system is in a great need. In this study, the investigation of improving lithotripter was conducted in the three ways: the wide beamwidth, the suppression of the shielding bubbles, and the real-time monitoring of stone fragments. The wide beamwidth has been suggested to be one of the key parameters for improved stone comminution. We proposed a novel design of shifted reflectors which expanded the geometrical focus of lithotripter. By shifting the reflectors 5 mm apart and maintaining the similar peak positive pressure at focus (8.07±0.05 MPa vs. 7.90±0.11 MPa), the beamwidth changed from 8.7 mm to 10.2 mm. Furthermore, the new design increased the maximum tensile (7.55 MPa vs. 8.95 MPa) and shear (6.10 MPa vs. 7.76 MPa) stresses inside a spherical stone in a diameter of 10 mm. The collapse time of bubble cavitation at focus also increased from 127.6±5.4 μs to 212.7±8.2 μs. Owing to the enhancements of both stresses and cavitation, our new design of the shifted reflectors improved the fragmentation efficiency of stone comminution from 32.2±5.6% to 57.9±4.6% in a plaster-of-Paris phantom after 1000 shocks. The shielding bubbles induced by incident shock waves hinder the wave propagation, which reduces the total energy delivered to the target. A new method of expelling shielding bubbles by a low-intensity pulsed ultrasound (LIPUS) during lithotripsy was proposed and investigated. The influence of parameters such as intensity, duration, and time delay of LIPUS on the bubble expelling was studied using light transmission and high-speed photography. Promising results showed that LIPUS (intensity of 2 W/cm2 and duration of 500 ms) between each pulse of shock waves had excellent ability of expelling bubbles. The fragmentation efficiency of combined waves (shock wave plus LIPUS) increased about 2.6-fold (30.8±6.0% vs. 80.5±25.4%) compared to the treatment with shock waves alone. There is still no adequate method of monitoring the progress of shock wave lithotripsy in real time. Most of current clinical treatments deliver the fixed number of pulses for each treatment, but this simplex scheme is not applicable to varied stones. It commonly results in retreatment and renal injury. To monitor the stone fragments, an algorithm constructed by the time reversal operator was investigated. The number of non-zero eigenvalues of the time reversal operator indicated the number of scatterers. Different types of stone clusters were tested. Results showed that our algorithm could identify one and two stones efficiently. According to this study, the next-generation lithotripter may combine the shifted reflectors and expelling ultrasound to achieve good fragmentation efficiency of stone comminution, and apply the time reversal operator method to evaluate the stone fragments during lithotripsy in real time.